A De Novo multi-approaches multi-criteria decision making technique with an application in performance evaluation of material handling device. (September 2015) - Bairagi, Bipradas; Dey, Balaram; Sarkar, Bijan; Sanyal, Subir Kumar
Highlights: We propose a De Novo MCDM model (TPOP) for precise ranking and selection. We introduce advanced version of entropy weighting method. This model (TPOP) eliminates inappropriate weights distribution. This model (TPOP) overcomes the rank reversal of the conventional approaches. The new model (TPOP) assists and guides decision makers. Abstract: Application of multiple conventional approaches to a particular multi-criteria decision making (MCDM) problem often suffers rank reversal giving rise to confusion and ambiguity in appropriate decision making. To eradicate the confusion, this paper proposes a De Novo multi-approaches multi-criteria decision making method namely Technique of Precise Order Preference (TPOP). The TPOP first examines the inconsistency in the ranking order of the alternatives of a MCDM problem by using multiple conventional approaches. If inconsistency/rank reversal in ranking order of the alternatives exists then TPOP, using advanced version of entropy weighting method introduced in this research work, measures weights of the final selection values of conventional approaches. Subsequently, TPOP based on these weights and final selection values computes precise selection indices (PSI) that determines accurate ranking order for the alternatives. The proposed technique is illustrated by two real life examples on material handling device (MHD) ranking and selection problems. The first example is initially solved using five conventional integrated fuzzy multi-criteria decision making techniques (FMCDMs) whereas the second example is taken from previous researchers' works. The results obtained using TPOP justify the validity, applicability and requirements of the proposed technique. The study shows that the proposed multi-approaches, multi-criteria decision making technique can be a useful and effective model in MCDM.